2016
DOI: 10.15376/biores.11.4.8820-8830
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Adsorbable Organic Halogen Formation During the First Chlorine Dioxide Bleaching Stage of Eucalyptus Kraft Pulp

Abstract: The emission standard for adsorbable organic halogen (AOX) has been adjusted as a mandatory assessment indicator in the papermaking industrial pollutants emission standards of China. To provide a theoretical basis to reduce AOX formation, a kinetic model of the first chlorine dioxide bleaching stage (D0) is presented for elemental chlorinefree (ECF) bleaching of eucalyptus kraft pulp. . R 2 was greater than 0.9, which means that the model was shown to have high prognostic ability and feasibility. In the D0 sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Song et al constructed the kinetics of laccase-aided chlorine dioxide bleaching and discussed the effects of laccase dosage, hydrogen peroxide dosage, and reaction temperature on the AOX content . Other researchers developed kinetic models of the first or second chlorine dioxide bleaching stage to analyze the factors influencing the reaction rate of AOX. These studies have shown that AOX emissions can be predicted by the kinetic model of AOX formation, and the AOX emission can be decreased by adjusting the operating conditions based on the kinetic model. Barroca found that the amount of chlorine dioxide presented a nonlinear relationship with the decrease in the light absorption coefficient based on a kinetic model of AOX formation .…”
Section: Introductionmentioning
confidence: 99%
“…Song et al constructed the kinetics of laccase-aided chlorine dioxide bleaching and discussed the effects of laccase dosage, hydrogen peroxide dosage, and reaction temperature on the AOX content . Other researchers developed kinetic models of the first or second chlorine dioxide bleaching stage to analyze the factors influencing the reaction rate of AOX. These studies have shown that AOX emissions can be predicted by the kinetic model of AOX formation, and the AOX emission can be decreased by adjusting the operating conditions based on the kinetic model. Barroca found that the amount of chlorine dioxide presented a nonlinear relationship with the decrease in the light absorption coefficient based on a kinetic model of AOX formation .…”
Section: Introductionmentioning
confidence: 99%
“…Among these, bleaching is the central step [ 11 ]. Elemental chlorine-free (ECF) bleaching using chlorine dioxide is the primary bleaching method employed in mainstream bleaching technology [ 12 ]. This is because of the excellent selectivity of chlorine dioxide for the delignification of lignin [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some research about modeling, optimization of pulp bleaching had been done to reduce pollutant generation and bleaching costs in our previous work (Yin et al, 2018;Ma et al, 2020). At present, most of the studied focus on how to reduce AOX emissions theoretically in view of generation mechanism (Zhu et al, 2016(Zhu et al, , 2017Dai et al, 2016), and there are few studies on controlling AOX emissions by mathematical model. People payed more attention to control the bleaching reaction for reducing AOX production (Kaur et al, 2018;Zhang et al, 2018b), without considering reducing the components that may produce AOX from the source.…”
Section: Introductionmentioning
confidence: 99%